A handbook of natural beauty - Bakhru, H.K. (DR)
Summary: "Beauty and health go hand in hand. The finest cosmetics in the world cannot disguise the effects of poor nutrition, lack of sleep and exercise or too much stress. Beauty comes from within and it is reflected in clear skin, sparkling eyes, glossy hair and a fit, trim body. While it is not possible to change one’s features, a lot can be done to attain other basic elements of true beauty. In this book Dr. H. K. Bakhru has covered all aspects of beauty and prescribed methods for treating various problems connected therewith in a natural way. A Handbook of Natural Beauty is your guide to looking good, feeling good and staying fit the natural way, the healthy way. It will help you discover Why water do more for you than any skin cream A delicious way to prevent tooth decay How to prevent your hair from graying and a natural hair dye A humble herb which makes your facial more effective Exercises for a healthier, lovelier you And a lot more from the leading expert on nature care. Many have benefited greatly after reading this book and have succeeded in overcoming their beauty problems. You too, can be one of them." - Author (back cover note)